Carnosine as a protective metabolic mediator in inflammatory lung injury by inhibiting macrophage infiltration and M1-like polarization - Ruan, Lianjie; Lin, Dekai; Lin, Binqin; Zhan, Qingqing; Zheng, Lili; Lin, Dandan; Zhuang, Yaoning; Zeng, Yiming (Frontiers in Pharmacology, 2025)
BackgroundInflammatory lung injury is a common pathological feature of pneumonia caused by various infectious and non-infectious agents. However, metabolic regulators that can mitigate inflammation and immune cell infiltration in diverse lung injury models remain poorly understood.MethodsUsing targeted metabolomic profiling of lung tissues collected on day 5 from two distinct murine models of lung inflammation—lipopolysaccharide (LPS)-induced and papain-induced—we identified carnosine as a commonly downregulated metabolite in both models. To evaluate its therapeutic potential, we administered exogenous carnosine in both models and assessed its effects on body weight, inflammatory cytokine expression, and histopathological changes.ResultsCarnosine supplementation significantly improved body weight maintenance, reduced the expression of pro-inflammatory cytokines, and attenuated histological lung damage in both LPS- and papain-induced lung injury models. Flow cytometry analysis revealed that carnosine treatment markedly decreased pulmonary infiltration of macrophages and neutrophils. Multiplex immunofluorescence further demonstrated a significant reduction of macrophage accumulation in the peribronchial regions of the lung following carnosine administration. In vitro experiments using bone marrow–derived macrophages (BMDMs) confirmed that carnosine effectively suppressed LPS-induced inflammatory responses and inhibited polarization toward the M1-like macrophage phenotype.ConclusionOur findings identify carnosine as a protective metabolic mediator in inflammatory lung injury and demonstrate its capacity to alleviate pulmonary inflammation by modulating innate immune cell recruitment and macrophage polarization. These results highlight the translational potential of carnosine as a therapeutic agent for treating inflammatory lung diseases.